A Project Report on Matrix Approach to Fitter Analysis of Lifting Surface - BENJAMIN ROHIT, HARISH KUMAR, RAGHUNANDAN and SHOEB AHMED (2011)
INTERNAL GUIDE: R SHANMUGHAM, MVJCE
Keywords: Matrix Approach